Post-glacial melt generation in Southern Chile and the development of the Carrán-Los Venados Volcanic Field (40°20’S) - McGee, Lucy; Chamberlain, Katy J.; Reagan, Mark; Nowell, Geoffrey; Lara, Luis (Volcanica, 2026)
The Carrán-Los Venados volcanic field in southern Chile comprises small basaltic eruption centres of Holocene to historical ages. These centres are atop extensive, basaltic flows that erupted during late glacial or early postglacial times (< 14ka), marking a dramatic change in eruption style over a short space of time. Differences in trace element characteristics and U-series isotopes point to a dampened subduction influence in the melting environment of the older Basal Lavas. Th isotopes point to higher melting rates and more dominant decompression melting, which may be related to the deglaciation of southern Chile at this time. Olivine textures and chemistry suggest longer storage times for the Basal Lavas compared to the Holocene tephras. The historic eruptions have relatively homogeneous whole rock compositions, suggesting the development of a storage system in the lower crust. This may be the beginning of a thermal environment more akin to those of nearby stratovolcanoes.